Estudo sobre a percep????o de valor de jovens consumidores de produtos de luxo acess??vel - Miranda, Camila Moreira Almeida de (2015)
This paper seeks to explain the motivators of perceived value among young consumers who purchase affordable luxury branded goods. The main objective was to study the motivators of perceived value and more specifically: to identify the latent variables which affect the behavior of the young consumer of affordable luxury branded goods; to assess how the latent variables interfere with the young consumers??? perceived value of affordable luxury branded goods; to assess how young consumers??? perceived value affects their attitude, loyalty and repurchase intention; and finally, to provide a specific measurement model for this consumer group. The model is based on existing models by Vigneron and Johnson (1999), Wiedmann, Hennings and Siebels (2009) and Galhanone (2013). This is a descriptive study using a quantitative approach. Data was collected using a survey, based on previously tested and validated scales, which was completed by a sample group of 246 university students at a IFES in the state of Mato Grosso do Sul, Brazil. Structural equation modeling and confirmatory factor analisys using Smart-PLS software were used for statistical analysis. The results show a statistically significant correlation between perceived value of young people who consume products of affordable luxury with the variables identified in the study. These results contribute to an understanding of the world of luxury of these youth and how they relate to brands. In general terms, the study offers useful tools for companies operating in the luxury market and tailoring their product offerings to their clients by helping them understand how a youth perceives a luxury product, and what the motivators are behind its purchase.